2019
DOI: 10.3390/ijms20030761
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals New Insights into the Bacterial Wilt Resistance Mechanism Mediated by Silicon in Tomato

Abstract: Bacterial wilt is a devastating disease of tomato caused by soilborne pathogenic bacterium Ralstonia solanacearum. Previous studies found that silicon (Si) can increase tomato resistance against R. solanacearum, but the exact molecular mechanism remains unclear. RNA sequencing (RNA-Seq) technology was used to investigate the dynamic changes of root transcriptome profiles between Si-treated (+Si) and untreated (−Si) tomato plants at 1, 3, and 7 days post-inoculation with R. solanacearum. The contents of salicyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 80 publications
(131 reference statements)
7
48
3
Order By: Relevance
“…However, many plant species particularly belonging to family brassicaceae [69], solanaceae [70], and Linaceae [71] does not carry any Si-transporter (NIP-III Aquaporin) and are known as poor Si accumulators. However, several reports suggesting Si derived benefits in such species make it more difficult to understand the molecular consequences [72,73]. So far, the Si-mediated mechanisms for the reduction of metal toxicity are less understood at the genetic and molecular levels.…”
Section: Silicon-mediated Mechanisms Of Metal Detoxificationmentioning
confidence: 99%
“…However, many plant species particularly belonging to family brassicaceae [69], solanaceae [70], and Linaceae [71] does not carry any Si-transporter (NIP-III Aquaporin) and are known as poor Si accumulators. However, several reports suggesting Si derived benefits in such species make it more difficult to understand the molecular consequences [72,73]. So far, the Si-mediated mechanisms for the reduction of metal toxicity are less understood at the genetic and molecular levels.…”
Section: Silicon-mediated Mechanisms Of Metal Detoxificationmentioning
confidence: 99%
“…These biotic stressors cause retardation of growth, yield production, and shortening of lifespan in hosts. According to the experimental studies, Si in plant roots can alleviate the stress after bacterial [140][141][142], fungal [143][144][145], insect [146,147], nematode [148,149], and plant [150,151] attack, but also stress from auto-toxicity of the same plant [152]. The level of its beneficial effect is Si concentration dependent.…”
Section: Effects Of Silicon In Plant Roots During Biotic Stressesmentioning
confidence: 99%
“…They improved the soil urease and soil acid phosphatase activity and caused a decrease in the numbers of wilt causing bacteria in both the soil [162] and the plants [156]. It has been shown that Si-mediated enhanced resistance and tolerance in tomato to R. solanacearum is associated also with differential expression of genes involved in pathogen-associated molecular pattern-triggered immunity via modification of signaling pathways and energy metabolism [141,142]. Coconut palms (Cocos nucifera) infected by phytoplasma that causes root wilt were able to influence the rhizosphere via secretion of compounds that promote beneficial microorganisms, such as N 2 -fixers, silicate solubilizers, and actinomycetes.…”
Section: Effects Of Silicon In Plant Roots During Biotic Stressesmentioning
confidence: 99%
“…Rapid changes in JA levels in the infected or damaged organs could be crucial for the plants to survive [35,38,39]. Several authors proved that JA accumulation and JA-mediated gene expression occur within several hours after the pathogen infection [65][66][67][68]. The results of Pozo et al [69] showed the transcript levels of the JA marker Lipoxygenase2 (LOX2) started to rise at 1 h after exogenous 50 mM MeJA treatment and reached the maximum at 6 h, but it significantly decreased after 12 h. Based on these observations, the effects of JA at the 6 th hour were selected to investigate the physiological role of JA under ER stress in more detail.…”
Section: Discussionmentioning
confidence: 99%